Perceptions about children’s and adolescents' mental health crisis interventions: a qualitative systematic review protocol (Research, Society and Development, 2023)
Introduction: many mental health issues begin in childhood and adolescence and this illness can impact adulthood. Considering that moments of crisis require adequate management so that the situation does not worsen, it is necessary to understand how the actors involved in child and adolescent mental health care have been happening. This review will be guided by the research question: “what are the perceptions of mental health professionals, family members, and users about interventions in mental health crises of children and adolescents in hospitals and community mental health services?”. Objective: to identify and synthesize available qualitative evidence on the perceptions mental health professionals, family members, and users have about interventions in the mental health crisis of children and adolescents. Methodology: this review will follow the JBI methodological guidelines. The search will be done in seven databases and gray literature. The study has no time limitation. Two independent reviewers will select and extract the data. In case of divergence, a third reviewer will be consulted. Final considerations: it is necessary to understand the perceptions of the actors involved on the subject so that practice, research, and policy recommendations are made to promote improvement in the care of children and adolescents in the crisis period.